Numerical Investigation of Compression Behavior of Bio-Inspired Honeycomb Designs - Solak, Alparslan (Fırat University, 2026)
This study numerically investigates the compressive behavior and energy absorption performance of bio-inspired honeycomb structures. A validated LS-DYNA finite element framework was first established for a regular hexagonal honeycomb and correlated with experimental results, showing good agreement in terms of force–strain response and deformation modes. Subsequently, seven bio-inspired configurations—spider, snail, wavy, bamboo, pomelo peel, grass stem, and hierarchical—were modeled under quasi-static compression. The results revealed that bio-inspired designs significantly influence deformation pathways and energy absorption capacity compared to the regular hexagon. Among the proposed designs, the pomelo peel, grass stem, and hierarchical honeycombs exhibited the highest specific energy absorption (7.88, 7.50, and 7.39 J/g, respectively), representing an improvement of up to 47% compared to the reference structure. This improvement is attributed to their multi-cell and hierarchical load-transfer mechanisms that delayed densification and ensured a prolonged plateau region. While spider and bamboo designs provided balanced performance with moderate specific energy absorption, the wavy and snail geometries demonstrated smoother plateau behavior with lower peak forces. Overall, the findings highlight that bio-inspired geometrical features can be effectively employed to enhance the crashworthiness of lightweight structures, offering valuable insights for future applications in transportation, packaging, and energy storage systems, and guiding the development of next-generation lightweight structural designs.

Bu çalışma, doğadan ilham alınmış bal peteği yapıların sıkıştırma davranışını ve enerji absorpsiyon performansını sayısal olarak incelemektedir. Düzenli altıgen bir bal peteği için doğrulanmış bir LS-DYNA sonlu elemanlar modeli oluşturulmuş ve deneysel sonuçlarla karşılaştırılmış, kuvvet–şekil değiştirme tepkisi ve deformasyon modları açısından iyi bir uyum elde edilmiştir. Ardından, örümcek, salyangoz, dalgalı, bambu, pomelo kabuğu, çim sapı ve hiyerarşik olmak üzere yedi farklı doğadan ilhamlı konfigürasyon yarı-statik sıkıştırma altında modellenmiştir. Sonuçlar, bu tasarımların deformasyon yolları ve enerji absorpsiyon kapasitesi üzerinde düzenli altıgen yapıya kıyasla önemli bir etkiye sahip olduğunu göstermektedir. Pomelo kabuğu, çim sapı ve hiyerarşik bal petekleri, çok hücreli ve hiyerarşik yük aktarım mekanizmaları sayesinde densifikasyonu geciktirerek uzun bir plateau bölgesi oluşturmalarıyla en yüksek özgül enerji absorpsiyon değerlerini (sırasıyla 7.88, 7.50 ve 7.39 J/g) göstermiş ve referans altıgen yapıya kıyasla %47'ye varan oranda performans artışı sağlamıştır. Örümcek ve bambu tasarımları orta seviyede özgül enerji absorpsiyonu ile dengeli bir performans sergilerken, dalgalı ve salyangoz geometrileri daha düşük tepe kuvvetleriyle daha düzgün plateau davranışı göstermiştir. Genel olarak, bulgular doğadan ilhamlı geometrik özelliklerin hafif yapılarda çarpışma dayanımını artırmak için etkili bir şekilde kullanılabileceğini ortaya koymakta; ulaştırma, paketleme ve enerji depolama sistemleri gibi gelecekteki uygulamalara değerli katkılar sunmakta ve yeni nesil hafif yapı tasarımlarına yön verecek bilgiler sağlamaktadır.
Doğadan İlhamlı Bal Peteği Tasarımlarının Sıkıştırma Davranışının Sayısal Olarak İncelenmesi
Keywords: Solid Mechanics; Katı Mekanik; Numerical Modelling and Mechanical Characterisation; Sayısal Modelleme ve Mekanik Karakterizasyon